PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA UPT KESMAS SUKAWATI II - Tirtaputra, I Putu Agus Ardi; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2016)
Their close relationship with subordinates made transformational leadership classified as effective leadership, because it can increase satisfaction and commitment level of subordinates. Job satisfaction and organizational commitment were critical factors to support organizational performance s . This study aimed to analyze the influence of transformational leadership and job satisfaction on organizational commitment in UPT Kesmas Sukawati II. Number of samples in this study were 65 employees. Data analy sis technique used in this study were path analysis. F indings of this study included : transformational leadership positive ly significant influencing job satisfaction ; transformational leadership positive ly significant influencing organizational commitment ; job satisfaction positive ly significant influencing organizational commitment.
Keywords: transformational leadership, organizational commitment, job satisfaction